Immune Challenges and Seizures: How Do Early Life Insults Influence Epileptogenesis? - Semple, Bridgette D.; Dill, Larissa K.; O'Brien, Terence J. (Frontiers in Pharmacology, 2020)
The development of epilepsy, a process known as epileptogenesis, often occurs later in life following a prenatal or early postnatal insult such as cerebral ischemia, stroke, brain trauma or infection. These insults share common pathophysiological pathways involving innate immune activation including neuroinflammation, which is proposed to play a critical role in epileptogenesis. This review provides a comprehensive overview of the latest preclinical evidence demonstrating that early life immune challenges influence neuronal hyperexcitability and predispose an individual to later life epilepsy. Here, we consider the range of brain insults that may promote the onset of chronic recurrent spontaneous seizures at adulthood, spanning intrauterine insults (e.g. maternal immune activation), perinatal injuries (e.g. hypoxic-ischemic injury, perinatal stroke) and insults sustained during early postnatal life – such as fever-induced febrile seizures, traumatic brain injuries, infections, and environmental stressors. Importantly, all of these insults represent immune challenges, triggering innate immune activation and implicating both central and systemic inflammation as drivers of epileptogenesis. Increasing evidence suggests that pro-inflammatory cytokines such as interleukin-1 and subsequent signaling pathways are important mediators of seizure onset and recurrence, as well as neuronal network plasticity changes in this context. Our current understanding of how early life immune challenges prime microglia and astrocytes will be explored, as well as how developmental age is a critical determinant of seizure susceptibility. Finally, we will consider the paradoxical phenomenon of preconditioning, whereby these same insults may conversely provide neuroprotection. Together, an improved appreciation of the neuroinflammatory mechanisms underlying the long-term epilepsy risk following early life insults may provide insight into opportunities to develop novel immunological antiepileptogenic therapeutic strategies.